On the performance of web services - Zahir Tari (Springer, 2011)
Provides innovative techniques to improve the performance of Web Services, as well as QoS (Quality of Service) requirements. The author presents two levels of Web Services: the "kernel" (the SOAP engine which delivers messages from one point to another through various networks), and the "server side" (which processes heavy load / requests)